Implikasi Aksiologi Matematika dalam Pendidikan - Edy Saputra; Rahmy Zulmaulida; Sarah (Jumper: Journal of Educational Multidisciplinary Research, 2025)
This research investigates the concept of Mathematical Axiology and its relation to mathematics education. Mathematical Axiology is a branch of mathematical philosophy that deals with the values, ethics, and principles underlying mathematics. This study aims to provide a brief overview of the importance of understanding mathematical axiology in the context of mathematics education. The research method used is a literature study with qualitative analysis of relevant sources. The results of this study reveal that understanding mathematical axiology has significant implications in mathematics education. It helps in promoting mathematical values, such as beauty and relevance, and developing mathematical ethics in problem-solving and decision-making. In addition, this study identifies recent developments in mathematical axiology, including the exploration of mathematical values in everyday life, ethics in algorithm development, and the link between mathematical axiology and student character development. The conclusion of this study is that mathematical axiology is an important aspect of mathematics education that can help create a generation that thinks critically, ethically, and understands mathematical values in a variety of contexts. The results of this study can provide guidance for mathematics educators, researchers, and policymakers in developing more holistic and relevant educational approaches to mathematics teaching.